A Short History of the Gender Wage Gap in Britain - Alex Bryson; Heather Joshi; Bożena Wielgoszewska; David Wilkinson (Institute of Labor Economics (IZA), 2020)
After shrinking dramatically during World War Two the gender wage gap (GWG) narrowed again in the early 1970s due to the Equal Pay Act. The GWG has closed across birth cohorts at all points in the adult life-cycle but remains. Within birth cohort it rises to middle age before falling again. Among those born in 1958, the raw GWG was 16 percentage points among workers aged 23, rising to 35 percentage points at 42. Among those born in 1970 the gaps were 9 and 31 percentage points at age 26 and age 42 respectively. Differences in men's and women's work experience in mid-life account for much but not all of the raw gap in both cohorts. The GWG is a little larger early in the life cycle when accounting for non-random selection into employment but selection plays no role later in life. Policy options for closing the remaining gap are considered.
Keywords: J16; J2; J3; 330; gender wage gap; labour force participation; birth cohorts; employment selection; sample attrition